Sosialisasi Kampus Universitas Islam Batang Hari yang Berkompetitif dan Berkarakter di Kabupaten Batang Hari - Adang Ridwan; Ria Krmila; Oryza Syavita; Hilda Rahman (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This study aims to determine the socialization of the competitive and characterful campus of the Islamic University of Batang Hari in Batang Hari Regency, Jambi Province in accepting new students. The method used is a descriptive qualitative method. The results of the study indicate that this socialization took place in several areas in Batin XXIV District, Batang Hari Regency, Jambi. This activity was held at SMK N 3 Batang Hari, SMA N 3 Batang Hari and SMA N 9 Batang Hari. In general, this socialization aims to provide an understanding to class XII students who plan to continue their education to college. Specifically, this activity also aims to increase the interest of prospective new students to register at the Islamic University of Batang Hari. The methods used in this socialization include lectures, discussions, as well as question and answer sessions and FGDs. It is hoped that through this activity, students' interest in continuing their education to college can increase, especially for those in Batang Hari Regency, Jambi ir, which is relatively close to the Islamic University of Batang Hari.